Helicobacter pylori Eradication in Parkinson's Disease: A Randomized Placebo‐Controlled Trial. Issue 12 (7th September 2020) - Tan, Ai Huey; Lim, Shen‐Yang; Mahadeva, Sanjiv; Loke, Mun Fai; Tan, Jiun Yan; Ang, Ban Hong; Chin, Kok Ping; Mohammad Adnan, Amni Fatihah; Ong, Shawna Mei Chien; Ibrahim, Aimi Izzah; Zulkifli, Nusyaibah; Lee, Jing Kun; et al.
ABSTRACT: Background: Helicobacter pylori (HP) infection has been associated with worse motor function in Parkinson's disease (PD). Objective: We aimed to evaluate the effects of HP eradication on PD symptoms. Methods: In this parallel‐group, double‐blind, randomized placebo‐controlled, single‐center trial, patients with PD with positive HP urea breath test and serology were block randomized (1:1) to receive standard eradication triple therapy or identically appearing placebo capsules for 1 week. Prespecified motor (International Parkinson and Movement Disorder Society Unified PD Rating Scale [MDS‐UPDRS], timed tests, and home‐based wearable sensor measurements), nonmotor (Leeds Dyspepsia Questionnaire and Montreal Cognitive Assessment), and quality‐of‐life (Parkinson's Disease Questionnaire‐39) outcome measures were assessed at weeks 6, 12, 24, and 52. The primary outcome was the baseline‐to‐week 12 change in ON medication MDS‐UPDRS motor scores. Lactulose‐hydrogen breath testing for concomitant small intestinal bacterial overgrowth was performed at baseline and repeated at week 24, together with the urea breath test. Results: A total of 310 patients were screened for eligibility and 80 were randomly assigned, of whom 67 were included in the full‐analysis set (32 treatment group patients, 35 placebo patients). HP eradication did not improve MDS‐UPDRS motor scores at week 12 (mean difference 2.6 points in favor of placebo, 95% confidence interval: −0.4 to 5.6, P = 0.089). There was no significant improvement in any motor, nonmotor, or quality‐of‐life outcome at weeks 12 and 52. Both the full‐analysis and per‐protocol analyses (based on eradication status) supported these conclusions. Small intestinal bacterial overgrowth status did not influence treatment results. Conclusions: HP eradication does not improve clinical outcomes in PD, suggesting that there is no justification for routine HP screening or eradication with the goal of improving PD symptoms. © 2020 International Parkinson and Movement Disorder Society